Reforma tributaria y su incidencia en las organizaciones de la economía popular y solidaria del cantón Bolívar, provincia de Manabí - Pillasagua Choez, Fernando Julio Christian (2024)
The present work focused on the analysis of the recent tax reforms in Ecuador and their impact on the organizations of the Popular and Solidarity Economy (EPS) in the Bolívar canton of the province of Manabí. The study employed a descriptive and quantitative approach, with data collected through document analysis and surveys to explore the problem and determine critical factors. Recent tax reforms include the Organic Law for Economic Development and Fiscal Sustainability (LODESF, 2021), which introduces changes to the taxation of income and assets, and the creation of the Regime for Entrepreneurs and Popular Companies (RIMPE); Among the expected benefits are the ease of tax compliance for small taxpayers, the tax presumption applied to the IR of the OEPS and the simple rules for calculating tax payments. The applicability of the LODESF makes it easier for organizations to declare semi annually, although the calculation is made on gross income and not on profits. This applicability develops the possibility of opportunities for organizations, fundamentally those belonging to the microbusiness sector, where dynamism is developed in the economy, job creation and taxation. Consequently, it is considered that the applicability of the reformed instruments is viable and facilitates the management of tax payments of organizations in the context of the EPS of Ecuador. Socioeconomically, the research showed three indicators of financial profitability with dynamic flows, positive and negative results of indistinct trend; while for ROS and ROA it was positive by 3 and 18% respectively, in the case of ROE it was negative by 5%. Other positive indicators for the OEPS sector were available capital, which increased by 2%, while dividends increased by 1%, the number of employees required grew by 7%, while the expense item per payroll increased by 2%, which is socioeconomically significant due to the existence of demand for labor.